Social media and hidden curriculum: What do teacher-student interactions teach students? - Mustafa Demir; Süleyman Nihat Şad (Elementary Education Online, 2023)
The aim of this study is to examine the views of the students about the learning outcomes of teacher-student interactions on social media within the context of hidden curriculum. To this end, a quantitative associational research design was used in this study. Within the scope of the research, 2046 students attending to the middle schools in Kahramanmaraş province were selected into the sample. The data of the study were collected using “Hidden curriculum on social media scale” which has a four-factor structure consisting of 16 items developed by the researchers. The results of the analysis from the hidden curriculum perspective revealed that as a result of interactions between the teacher and the student on social media, students learn some rules and values, know better about their teachers, restrain themselves from sharing and communicating about certain topics, and gain confidence in communication. Furthermore, a statistically significant difference was found in favor of male students in terms of learning to restraint and gaining confidence in communication, whereas no significant difference was observed in terms of learning rules and values, and knowing better about teachers. With regard to grade level, the learning outcomes of especially the 5th graders through hidden curriculum on social media were found to be significantly more than those of other students in upper classes of middle schools. However, all the statistically significant differences were found to have small effect sizes. It was also found that the daily time students spend on social media and the number of teachers added as friends to their accounts were significant predictors of students’ their learning outcomes within the scope of hidden curriculum.